Renal Function Evaluation of Hypertensive Patients by Renogram in a Teaching Hospital (Faridpur Medical College Journal, 2016)
Arterial Hypertension is the most common cardiovascular disease and is a major public health problem in both developed and developing countries. The aim of the study was to assess renal involvement in hypertensive patient by renogram, which is not detected by conventional biochemical test. This was a cross sectional observational study. Consecutive 30 hypertensive patients admitted in the medicine wards from March, 2006 to April, 2007 in Rajshahi Medical College Hospital, Bangladesh were taken as case. Informed consent was taken from all the study patients or from their attendants. Detail history was taken from each patient or from their attendants' then clinical examination and relevant investigations were done. Emphasis was laid to find out renal involvement in long standing hypertensive patients by renogram. After initial selection; laboratory investigations like Urine for R/M/E, Blood Sugar 2ABF, S. Creatinine, USG of KUB, ECG and Hb% were done for every patients. All patients included in this study renogram were done. Majority of the patient (40%) were between the age of 41-50 years and Male: Female ratio was 3:2. Most of the patient lead a moderately active life (66.67%). Serum Creatinine was raised in 23.33% patient whereas renal parenchymal insufficiency evidenced by renogram was found in 50% case. In this study, we found that a significant number of cases (26.67%) having renal parenchymal insufficiency were not detected by S. Creatinine level, but detected by renogram. Renogram is superior to conventional biochemical renal function test for early detection of hypertensive nephropathy.Faridpur Med. Coll. J. Jan 2016;11(1): 11-14